The effect of socio-economic deprivation on severity of glaucoma at presentation. Issue 1 (23rd July 2009) - Ng, W S; Agarwal, P K; Sidiki, S; McKay, L; Townend, J; Azuara-Blanco, A
Abstract : Objective: To evaluate the influence of socio-economic factors on severity of glaucoma at presentation Methods: All newly diagnosed glaucoma patients at the University Hospitals-NHS, Aberdeen and South Glasgow University Hospitals-NHS, in 2006, were included. Glaucoma was severe at presentation if there was a repeatable visual-field loss with a mean deviation index greater than 12 dB in the Humphreys visual fields test or an absolute paracentral scotoma within the central 5° of the visual fields. Home address was used to determine the Scottish Index of Multiple Deprivation (SIMD) rank. The SIMD rank, demographics and severity of glaucoma at presentation were investigated using general linear modelling. Results: There were 48 patients with severe glaucoma and 74 patients with non-severe glaucoma. In four, the severity could not be determined. Severity of glaucoma at presentation was significantly associated with SIMD rank, being most severe in patients from areas with the lowest ranks (p = 0.026). Age was a significant factor (p = 0.024), with severe glaucoma being more common in elderly patients. Conclusions: Age and socio-economic deprivation were associated with severity of glaucoma at presentation, with patients from areas of higher socio-economic deprivation presenting with more advanced glaucoma.